Pla/Organoclay Bionanocomposites Impregnated with Thymol and Cinnamaldehyde by Supercritical Impregnation for Active and Sustainable Food Packaging - Valenzuela-Bascunan, X; Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Riveros-Faba, S; Villegas-Vallejos, C (Elsevier Ltd, 2019)
Bionanocomposite films based on poly (lactic acid) (PLA) reinforced with nanoclay C30B (5.0% w/w) were impregnated with thymol (Thy) and cinnamaldehyde (Ci), incorporated through supercritical impregnation using carbon dioxide (scCO2). These assays were implemented at a pressure of 12 MPa, a constant temperature equal to 40 °C and a despressurization rate of 1.0 MPa min−1. Depending on the active compound incorporated into the films, the concentrations varied from 11 to 17 %w/w. The adittion the both active compound and the nanoclay caused different changes in the structural, thermal, mechanical and antibacterial properties of the final materials. The results showed diferent effect in the distint properties and the strong antibacterial activity against the selected gram positive and gram negative microorganisms. Finally, we assayed the bionanocomposites disintegration under composting conditions at laboratory scale level, which was evaluated by monitoring their weight loss at different times of disintegration: 1, 4, 7 and 14 days. All bionanocomposites were fully disintegrated in compost showing their possible application as compostable flexible active films. © 2019 Elsevier Ltd